Decolonizing Foreign Language Education: The Misteaching of English and Other Colonial Languages - DeGraff, Michel (Series in Critical Narrative, 2019)
Decolonizing Foreign Language Education interrogates current foreign language and second language education approaches that prioritize white, western thought. Edited by acclaimed critical theorist and linguist Donaldo Macedo, this volume includes cutting-edge work by a select group of critical language scholars working to rigorously challenge the marginalization of foreign language education and the displacement of indigenous and non-standard language varieties through the reification of colonial languages. Each chapter confronts the hold of colonialism and imperialism that informs and shapes the relationship between foreign language education and literary studies by asserting that a critical approach to applied linguistics is just as important a tool for FL/ESL/EFL educators as literature or linguistic theory.